Psychometric Characteristics of the Intergroup Anxiety Scale among International Students in Indonesia - Nugraha Arif Karyanta; Suryanto Suryanto; Andik Matulessy (Green Publisher Indonesia, 2024)
When someone perceives significant differences in others, they may feel anxious about the potential for negative interactions or undesirable outcomes that may arise from such interactions. This is referred to as intergroup anxiety. It is important to research the validity and reliability of the intergroup anxiety scale for international students in Indonesia because intergroup anxiety affects various psychological variables in them. One of the most commonly used instruments to measure intergroup anxiety is the Intergroup Anxiety Scale (IAS) by Walter G. Stephan and Cookie White Stephan, developed since 1985. This study aims to evaluate the psychometric properties of the IAS in the context of international students in Indonesia. From the analysis of 100 collected data points, the results show that the IAS used in this study meets the criteria for content validity, construct validity, and reliability. The results indicate that the IAS meets four Goodness of Fit criteria, with RMSEA = 0.079, SRMR = 0.074, NFI = 0.90, and CFI = 0.95. Furthermore, the reliability of the IAS was evaluated with an Average Variance Extracted (AVE) value of 0.57. The overall Composite Reliability (CR) value reached 0.93. Therefore, it can be concluded that the IAS is a valid and reliable tool for measuring self-construal among international students in Indonesia.